PARENTAL RESPONSIBILITY FOR CHILDREN'S MENTAL HEALTH IN MUSLIM FAMILIES IN SINGAPORE: AN ANALYSIS BASED ON HIFZ AL-NASL THEORY - Muhammad Norikqaf Bin Mohd Roslee; Bagus Ramadi (Program Pascasarjana UIN Sumatera Utara, 2026)
Recent national data indicate a serious mental health crisis among youth in Singapore. The National Youth Mental Health Study conducted by the Institute of Mental Health reported that 30.6% of youths aged 15–35 experienced severe or extremely severe symptoms of depression, anxiety, and/or stress. In addition, suicide remains the leading cause of death among youths aged 10–29, with 314 suicide cases recorded in 2023 by Samaritans of Singapore. These statistics also include youths from Muslim families, indicating that religious identity alone does not prevent mental health disorders. This study examines parental responsibility for children’s mental health within Muslim families in Singapore through the framework of Hifz al-Nasl, one of the objectives of Islamic law (*maqasid al-shari‘ah*). Using an empirical juridical approach grounded in Islamic legal theory, this qualitative field research explores how parents understand and practice their responsibilities toward the psychological, emotional, and spiritual well-being of their children. The study finds that Hifz al-Nasl extends beyond the preservation of biological lineage to include mental and emotional protection necessary for establishing *sakinah* and *mawaddah wa rahmah* within Muslim families. The study recommends strengthening mental health literacy and faith-based parenting practices in Muslim households in Singapore.